Balanced SSFP-like steady-state imaging using small-tip fast recovery (STFR) with a spectral pre-winding pulse - SUN, HAO (Magn Reson Med, 2015)
PURPOSE: Small-tip fast recovery (STFR) imaging has been proposed recently as a potential alternative to balanced steady-state free precession (bSSFP). STFR relies on a tailored “tip-up” RF pulse to achieve comparable signal level as bSSFP, but with reduced banding artifacts and transient oscillations, and is compatible with magnetization-preparation pulses. Previous STFR implementations used 2D or 3D pulses spatially tailored to the accumulated phase calculated from a B0 field map, making the steady-state STFR signal contain some T2* weighting. Here we propose to replace the spatially tailored pulse with a recently introduced spectrally selective “pre-winding” pulse that is precomputed to a target frequency range. The proposed “spectral-STFR” sequence produces T2/T1-weighted images similar to bSSFP, but with reduced banding and potentially other benefits. THEORY AND METHODS: We investigated the steady-state signal properties of spectral-STFR using simulations, and phantom and human volunteer experiments. RESULTS: Our simulation and experimental results showed that the spectral-STFR sequence has similar signal level and tissue contrast as bSSFP, but has a wider passband and more consistent banding profiles across different tissues (e.g., less hyperintense signal at band edges for low flip angles). Care is needed in designing the spectral RF pulse to ensure that the small tip angle approximation holds during RF transmission. CONCLUSION: Spectral-STFR has similar tissue contrast as bSSFP but a wider passband and more consistent CSF/brain tissue contrast across the passband. The spectral-STFR sequence is a potential alternative to bSSFP in some applications. Compared to a spatially tailored STFR sequence, spectral-STFR can be pre-computed, is easier to implement in practice, and potentially has more uniform image contrast and minimal T2* weighting.